2004
DOI: 10.1021/nl048382k
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Conjugated-Polymer Light-Emitting Diodes

Abstract: We use e-beam lithography to pattern an indium tin oxide (ITO) electrode to create arrays of conjugated-polymer LEDs, each of which has a hole-injecting contact limited to 100 nm in diameter. Using optical microscopy, we estimate that the electroluminescence from a 100 nm diameter LED comes from a region characterized by a diameter of approximately 170 nm. This apparent broadening occurs due to current spreading within a PEDOT:PSS layer which was included to aid hole injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
65
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(66 citation statements)
references
References 26 publications
1
65
0
Order By: Relevance
“…Increasing attention devoted to the understanding of faradaic and interfacial charge transfer mechanisms in poly 3,4-(ethylenedioxythiophene) (PEDOT) films is due to the tremendous potential this polymer has for many practical applications such as sensors, supercapacitors, organic solar cells, electrochromic devices and light emitting diodes [1][2][3]. Although the electrical (conduction) properties, optical response and the electrochemical characteristics of PEDOT films grown by different routes has been studied rather exhaustively [4][5][6], the charge transfer events of the film when oxidized and reduced in electrolytes are relatively less explored.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing attention devoted to the understanding of faradaic and interfacial charge transfer mechanisms in poly 3,4-(ethylenedioxythiophene) (PEDOT) films is due to the tremendous potential this polymer has for many practical applications such as sensors, supercapacitors, organic solar cells, electrochromic devices and light emitting diodes [1][2][3]. Although the electrical (conduction) properties, optical response and the electrochemical characteristics of PEDOT films grown by different routes has been studied rather exhaustively [4][5][6], the charge transfer events of the film when oxidized and reduced in electrolytes are relatively less explored.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Polyaniline (PAN) is one of the most promising conducting polymers for its electronic, electrochemical, electrorheological and optical properties, good environmental and thermal stability, [6] and applications including catalyst, [7] light emitting diodes, [8] sensors, [9,10] gas separation membranes, [11] and electrorheological fluids. [12,13] However, the practical exploitation of PAN has been hampered to some extent because of its intractable nature, that is, its infusibility at melt processing temperature and poor solubility in common solvents except for H 2 SO 4 and N-methylpyrrolidone (NMP).…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have shown that the general morphology of polymers at the microscale and nanoscale can be obtained via utilizing top-down approaches such as photolithography, [3] soft-lithography [4] and electron-beam lithography. [5] However, these technologically top-down approaches tend to be complex and depend severely on the experimental instruments, thereby rendering the difficulty of well-defined morphology of polymer.…”
Section: Introductionmentioning
confidence: 99%